Photocatalysis: Microwave‐Induced Metal Dissolution Synthesis of Core–Shell Copper Nanowires/ZnS for Visible Light Photocatalytic H2 Evolution (Adv. Energy Mater. 22/2019). Issue 22 (12th June 2019) - Xiao, Shuning; Dai, Wenrui; Liu, Xiaoyan; Pan, Donglai; Zou, Hangjun; Li, Guisheng; Zhang, Guoqiang; Su, Chenliang; Zhang, Dieqing; Chen, Wei; Li, Hexing
Abstract : In article number1900775, Chenliang Su, Dieqing Zhang, Wei Chen, Hexing Li and co‐workers develop a microwave‐induced metal dissolution strategy for synthesizing copper nanowires/ZnS (CuNWs/ZnS) hybrids with a core‐shell structure. The super‐hot surfaces of CuNWs induced by the microwaves ensure the localized crystallization of ZnS which is doped with dissolved Cu + . The hybrids possess strong interfacial coupling and demonstrate a highest H2 evolution rate of 10 722 μmol h −1 g −1 among noble‐metal free visible‐light‐driven photocatalysts.